Tax Administration Reform in the Francophone Countries of Sub-Saharan Africa - Fossat, Patrick (IMF Working Papers; Working Paper ;, 2013)
Since the early 1990s, major tax administration reforms have been implemented in the Francophone countries of sub-Saharan Africa, with significant support from the IMF and development partners. While the reforms have contributed to an increase in revenues, attention is still needed to address a number of weaknesses in these countries' tax administrations. A review of the conditions for successful modernization of the tax administration shows that significant changes are needed to ensure better utilization of technical assistance, improve the governance of reforms, and provide the tax administrations with greater flexibility in managing their resources.